(untitled) (FUDMA JOURNAL OF SCIENCES, 2021)
Study was conducted on Floristic Composition and Diversity of Tree Species in Kumo Town and its Environs. The aim was to investigate the Tree Species Structure, composition and diversity. Systematic random sampling method was used to sample the Tree species. The result showed that a total number of Twenty –Seven (27) species belonging to 8 genera and 12 families were identified. The family Leguminosae: Mimosoideae had the highest number of 4 species. The family Combretaceae, Moraceae, Caesalpinoidceae, and Palmae had 3 species each. The family Anacaediaceae, Myrtaceae, were represented by 2 species each. The remaining 5 families; Balanitaceae, Bombacaceae, Meliaceae, Rhamnaceae and Sterculiaceae were represented by 1 species each. The plant with the highest dominance was Adansonia digitata. The Shannon Weiner index was 2.45 and Simpson index was 0.48. This study therefore concluded that the species Azadirachta indica was the most abundant, with highest Relative Density, Relative Frequency, and Importance Value Index in the study area. This study recommended that the plants that had the lowest IVI such as Prosopis africana, Cassia sieberiana, need urgent conservation measures